Zbrodnie przeciwko dziedzictwu kulturowemu przed Międzynarodowym Trybunałem Karnym – analiza krytyczna: [Cultural heritage crimes before the International Criminal Court – critical analysis] (Studia Prawnicze / The Legal Studies, 2016)
W dniu 24 marca 2016 r. MTK wydał postanowienie potwierdzające zarzuty wobec Ahmada Al Faqi Al Mahdi (Abu Touraba), domniemanego bojownika Ansar Dine, islamistycznego ugrupowania, działającego w ścisłej współpracy z liderami Al-Kaidy w Islamskim Maghrebie (AQIM) w ramach struktur represji i terroru ustanowionych przez te grupy w Timbuktu. Jest on podejrzewany o popełnienie zbrodni wojennych polegających na zamierzonym kierowaniu ataków na budynki, nie będące celami wojskowymi, przeznaczone na cele religijne, edukacyjne, artystyczne, naukowe lub charytatywne oraz pomniki historyczne w Timbuktu latem 2012 r., w myśl postanowień art. 8(2)(e)(iv) Statutu MTK (Statut Rzymski). Abu Tourabowi zarzuca się, że stał na czele grupy odpowiedzialnej za wykonanie decyzji islamskiego trybunału Timbuktu, w której nakazano zniszczenie zabytków tego miasta. Podnoszone jest, że jego czyny przeciwko słynnym muzułmańskim zabytkom kultury subsaharyjskiej Afryki były kiero-wane współczesną wersją ikonoklazmu – terroryzmu kulturowego skierowanegoprzeciwko dziełom sztuki, symbolom bałwochwalstwa – ideologii głoszonej wielokrotnie przez różne grupy ekstremistyczne od Syrii po Nigerię, szukające rozgłosu lub uznania. Ich zdaniem, ta ideologia „usprawiedliwia” ataki oraz grabież dziedzictwa kulturowego. On 24 March 2016 the International Criminal Court (ICC) issued a decision confirming the charges of committing war crimes by Al Ahmad Al Mahdi (Abu Tourab). He is suspected of war crimes allegedly committed in 2012, in Timbuktu (Mali), through intentionally directing attacks against buildings dedicated to religion and/or historical monuments (Article8(2)(e)(iv) of the Rome Statute). In fact, this is the first case to be brought before the ICC concerning the destruction of cultural property. By referring to the circumstances of the case, this article analyses the complimentary function of international criminal tribunals in the prosecuting and convicting of individuals liable for grave cultural heritage crimes vis-à-vis the shortcomings of national criminal jurisdiction. First, it reconstructs the normative foundations of prohibiting and prosecuting cultural heritage crimes. Second, it endeavours to critically assess the practice of international criminal tribunals ad hoc in dealing with the destruction of cultural property. In particular, by referring to certain cases adjudged by the ICTY, it aims to demonstrate to what extent the international protective status of a cultural heritage site may constitute a critical factor in imposing criminal responsibility on individual perpetrators (the cases of Blaškić, Čerkez and Strugar). It also analyses whether intentional attacks against cultural heritage sites, whose protection lies in the general interest of all humanity, may have an impact on the gravity of the crime and the penalty imposed for its commission. Third, the paper deals with the limited provisions of the Rome Statute and offers some general conclusions in respect to the evolving system of individual criminal responsibility for cultural heritage crimes.